Reconditioning by end‐ischemic hypothermic in‐house machine perfusion: A promising strategy to improve outcome in expanded criteria donors kidney transplantation. Issue 3 (March 2017) - Gallinat, Anja; Amrillaeva, Vera; Hoyer, Dieter P.; Kocabayoglu, Peri; Benko, Tamas; Treckmann, Jürgen W.; van Meel, Marieke; Samuel, Undine; Minor, Thomas; Paul, Andreas
Abstract: This clinical study evaluates end‐ischemic hypothermic machine perfusion (eHMP) in expanded criteria donors (ECD) kidneys. eHMP was initiated upon arrival of the kidney in our center and continued until transplantation. Between 11/2011 and 8/2014 eHMP was performed in 66 ECD kidneys for 369 (98‐912) minutes after 863 (364‐1567) minutes of cold storage (CS). In 49 of 66 cases, the contralateral kidney from the same donor was preserved by static CS only and accepted by another Eurotransplant (ET) center. Five (10.2%) of these kidneys were ultimately judged as "not transplantable" by the accepting center and discarded. After exclusion of early unrelated graft losses, 43 kidney pairs from the same donor were eligible for direct comparison of eHMP vs CS only: primary non‐function and delayed graft function (DGF) were 0% vs 9.3% ( P =.04) and 11.6% vs 20.9% ( P =.24). There was no statistically significant difference in 1‐year graft survival (eHMP vs CS only: 97.7% vs 88.4%, P =.089). In a multivariate analysis, eHMP was an independent factor for prevention of DGF (OR: 0.28, P =.041). Development of DGF was the strongest risk factor for 1‐year graft failure (Renal resistance: 38.2, P <.001). In summary, eHMP is a promising reconditioning technique to improve the quality and acceptance rate of suboptimal grafts.